2013
DOI: 10.1016/j.bmcl.2012.12.032
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficiency of 9-(N-cinnamoylbutyl)aminoacridines against blood- and liver-stage malaria parasites

Abstract: a b s t r a c tNovel 9-aminoacridine derivatives were synthesized by linking the heteroaromatic core to different cinnamic acids through an aminobutyl chain. The test compounds demonstrated mid-nanomolar in vitro activity against erythrocytic stages of the chloroquine-resistant W2 strain of the human malaria parasite Plasmodium falciparum. Two of the most active derivatives also showed in vitro activity against liver-stage Plasmodium berghei, with activity greater than that of the reference liver-stage antimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Relevantly, mepacrine-CA conjugates (12, where R 1 = OMe, R 2 = Cl) displayed more potent dual-action activity than their unsubstituted acridine counterparts (12, where R 1 = R 2 = H), being 2-to 4-fold more active than the reference primaquine against liver-stage parasites (1.6 < IC 50 < 4.9 µM versus 7.5 µM for primaquine), equipotent to chloroquine against blood forms of P. falciparum 3D7 (77 < IC 50 < 39 nM versus 21 nM for chloroquine), and 2-to 4-fold more active than chloroquine against blood forms of P. falciparum Dd2 (29 < IC 50 < 131 nM versus 108 nM for chloroquine). Moreover, as compared to the parent mepacrine, some of its CA conjugates were more active and less cytotoxic to human cells [64,65]. The same authors later found that replacing the CA building block by other moieties led to slightly increased cytotoxicity and somewhat decreased activity [66].…”
Section: Cinnamic Acid Conjugation In the Rescuing Of Classical Antimmentioning
confidence: 98%
See 2 more Smart Citations
“…Relevantly, mepacrine-CA conjugates (12, where R 1 = OMe, R 2 = Cl) displayed more potent dual-action activity than their unsubstituted acridine counterparts (12, where R 1 = R 2 = H), being 2-to 4-fold more active than the reference primaquine against liver-stage parasites (1.6 < IC 50 < 4.9 µM versus 7.5 µM for primaquine), equipotent to chloroquine against blood forms of P. falciparum 3D7 (77 < IC 50 < 39 nM versus 21 nM for chloroquine), and 2-to 4-fold more active than chloroquine against blood forms of P. falciparum Dd2 (29 < IC 50 < 131 nM versus 108 nM for chloroquine). Moreover, as compared to the parent mepacrine, some of its CA conjugates were more active and less cytotoxic to human cells [64,65]. The same authors later found that replacing the CA building block by other moieties led to slightly increased cytotoxicity and somewhat decreased activity [66].…”
Section: Cinnamic Acid Conjugation In the Rescuing Of Classical Antimmentioning
confidence: 98%
“…The strategy of conjugation to CA in an effort to rescue drugs that are no longer in use as antimalarials has also been applied to mepacrine, or quinacrine (4), the first synthetic drug developed purposely for malaria [63]. Thus, Gomes and co-workers developed conjugates 12 ( Figure 5), whose in vitro activity was assessed against liver-stage P. berghei parasites and blood-stage P. falciparum parasites of both a chloroquine-sensitive (3D7) and a chloroquine-resistant (Dd2) strain [64,65]. Relevantly, mepacrine-CA conjugates (12, where R 1 = OMe, R 2 = Cl) displayed more potent dual- The strategy of conjugation to CA in an effort to rescue drugs that are no longer in use as antimalarials has also been applied to mepacrine, or quinacrine (4), the first synthetic drug developed purposely for malaria [63].…”
Section: Cinnamic Acid Conjugation In the Rescuing Of Classical Antimmentioning
confidence: 99%
See 1 more Smart Citation
“…The acridine‐cinnamic acid hybrids 72 (IC 50 : 126‐892 nM against CQR W2 strain) and 73 (IC 50 : 3.2‐131.0 nM) also demonstrated potential antiplasmodial activity against CQS 3D7, CQR W2, Dd2 strains of P falciparum , and liver‐stage P berghei strain, and hybrids 73 were more potent than the corresponding analogs 72 , indicating substituents on the acridine moiety contributed greatly to the activity . For hybrids 73 , electron‐donating alkyl methyl and iso‐propyl were more favorable than electron‐withdrawing fluoro and bromo against CQS 3D7, CQR W2 and Dd2 strains.…”
Section: Quinoline Hybridized With Novel Antimalarial Pharmacophores mentioning
confidence: 99%
“…Those biological activities have been reported in many scientificp apers. Moreover,c innamamide derivatives have been shown to possess tyrosinase inhibitory, [7,8] antimalarial, [9,10] and in vitro anti-atherosclerotic activities. [11] Cinnamamide derivatives have been also widely evaluated for potential activity in both the peripheral and central nervous systems, including antiepileptic, antidepressant, neuroprotective, analgesic, anti-inflammatory,m uscle relaxant, and sedative/hypnotic properties.…”
Section: Introductionmentioning
confidence: 99%